Twitter analysis shows immigration drove UK leave voters. (Research'eu results magazine)
Six months on from the UK's decision to leave the European Union, researchers are still trying to ascertain how and why the Leave campaign was ultimately victorious. In new research partly supported by the EU-funded PHEME and SOBIGDATA projects, 3 million tweets were analysed over a 6 month period that showed immigration was by far the most important issue driving Leave voters.